Cardiac Arrhythmia in a Patient with Sickle Cell Anemia and Falciparum Malaria Treated with Intravenous Artesunate - Abdulrahman Hummadi; Sultan Mubarki; Ayel yahay; Awad Mohammed Al-Qahtani (Case Reports in Infectious Diseases)
Treatment of severe malaria with artemisinin derivatives in patients with comorbid conditions such as sickle cell anemia must be considered with precaution. We report here a case of possibly undocumented ventricular arrhythmia in a sickle cell anemia patient diagnosed with Plasmodium falciparum malaria and treated with intravenous artesunate. The patient suffered from wide complex tachycardia after treatment with artesunate 170 mg (2.4 mg/kg) i.v. bolus, tachycardia was managed with amiodarone (150 mg i.v. for 10 minutes). Electrocardiographic abnormalities, including QT prolongation, are common in patients with sickle cell anemia. The mortality rate in sickle cell anemia patients due to cardiovascular and pulmonary complications remains high. The probability of precipitation of ventricular arrhythmias may increase in patients with sickle cell anemia, diagnosed with malaria and treated with artemisinin derivatives.